Adverse impact of elevated serum progesterone and luteinizing hormone levels on the hCG trigger day on clinical pregnancy outcomes of modified natural frozen-thawed embryo transfer cycles - Huang, Chenyang; Shen, Xiaoyue; Shi, Qingqing; Shan, Huizhi; Yan, Yuan; Liu, Jingyu; Kong, Na (Frontiers in Endocrinology, 2022)
Research question The relationship between serum progesterone (P) and luteinizing hormone (LH) levels on the human chorionic gonadotropin (hCG) trigger day and the clinical pregnancy outcomes in modified natural frozen-thawed embryo transfer (mNC-FET) cycles are controversial. Design This was a retrospective study of 788 mNC-FET cycles. A smooth fitting curve and threshold effect analysis was performed to identify the effect of serum P and LH levels measured on the hCG day on the clinical pregnancy rate (CPR) and live birth rate (LBR) of mNC-FET cycles. Results The CPR and LBR decreased significantly when the LH level on the hCG day was greater than or equal to 32 IU/L. Further subgroup analysis showed that the CPR decreased significantly when the P level on the hCG day was equal to or greater than 1 ng/mL. When the P level was lower (< 1 ng/mL), the patients with an LH level greater than or equal to 32 IU/L had reduced CPR and LBR in mNC-FET cycles. Conclusion Applying the hCG trigger on a day with a higher P level (≥ 1 ng/mL) leads to a decreased CPR and LBR. hCG administration with a higher LH level (≥ 32 IU/L) also leads to a decreased CPR and LBR in mNC-FET cycles when the P level is less than 1 ng/mL.